Does the Use of Solar and Wind Energy Increase Retail Prices in Europe? Evidence from EU-27. (November 2015) - Sisodia, Gyanendra Singh; Soares, Isabel; Ferreira, Paula; Banerji, Sanjay; Van den Poel, Dirk; Kumar, Manish
Abstract: High technology and innovation market risk make renewable electricity generation expensive. On the other hand, green taxes applied to thermal generation also play a significant role in the increasing retail prices, considering that most energy systems are not completely renewable. The academic literature on the relationship between renewable electricity supply and electricity prices to final consumers suggest that a larger share of renewable electricity supply increases the price of electricity to end consumers although wind energy and solar energy have very low marginal costs. This study shows the individual contribution of solar and wind energy generation to the households and industrial electricity retail prices through panel data modeling of EU-27 (1995 to 2011). Random effect modeling was applied to understanding the net effect on prices. Independent variables include regulation perceptions, carbon emissions and levelised costs of electricity generation. The result of this study suggests that energy generation through wind and solar plays a negligible role in determining retail electricity prices to households, whereas in the case of industrial prices, their (solar and wind's) contribution is significant, but the value of the coefficient observed is close to zero.